2018
DOI: 10.26417/ejms.v3i3.p74-79
|View full text |Cite
|
Sign up to set email alerts
|

How Can Social Media Be Helpful for Immigrants to Integrate Society in the US

Abstract: With an increase in diversity in the society, the United States has been faced with the challenge of how to integrate its immigrants in the American communities. Different researches have shown that social media has a significant role in the integration of these immigrants. However, that which has been missing in such studies encompasses the conceptual frameworks for understanding the existing interplay between the utilization of social media and, on the other hand, integration. The results of this research po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In a previous study, immigrants found government websites to be difficult to navigate and instead preferred social media for its ease and clarity. 72 Given the prevalence of misinformation on social media, 73 74 and its detrimental impact, 75 there is an opportunity to develop trustworthy, reliable digital resources to provide information about public benefits for refugees and asylum seekers. Such information should be up-to-date with accurate legal information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, immigrants found government websites to be difficult to navigate and instead preferred social media for its ease and clarity. 72 Given the prevalence of misinformation on social media, 73 74 and its detrimental impact, 75 there is an opportunity to develop trustworthy, reliable digital resources to provide information about public benefits for refugees and asylum seekers. Such information should be up-to-date with accurate legal information.…”
Section: Discussionmentioning
confidence: 99%
“…More than half of the participants in this study used internet sources to learn about their eligibility for public benefits. In a previous study, immigrants found government websites to be difficult to navigate and instead preferred social media for its ease and clarity 72. Given the prevalence of misinformation on social media,73 74 and its detrimental impact,75 there is an opportunity to develop trustworthy, reliable digital resources to provide information about public benefits for refugees and asylum seekers.…”
Section: Discussionmentioning
confidence: 99%
“…Social media can also facilitate the development of social networks in the new environment. thus helping them to better adapt to the cultural environment of the host country [7]. Through interpersonal communication and participation in social activities through social media, they can obtain high-quality communication across regions and cultures, which effectively reduces the pressure of cultural adaptation in the host country and helps them to obtain more entertainment and a sense of belonging to the group [8].On the other hand, some scholars have suggested that the use of social media has a negative impact on the individual's cross-cultural adaptation and that the use of social media for cross-cultural adaptation of migrants will enhance their understanding of the cultural environment of the host country [9].…”
Section: Rationale and Mechanismsmentioning
confidence: 99%
“…Media and communication technologies have historically played a crucial role in the lives of people on the move and the existing literature has mapped the ways in which these communities incorporate digital technologies and the implications on their lives (see Alencar, 2018, 2020; Leurs and Ponzanesi, 2018; Retis and Tsagarousianou, 2019, for an overview). Recent work examines how social media facilitate migration and integration (Alencar, 2018; Erdem, 2018), human trafficking (Zimmerman and Kiss, 2017) and diaspora engagement (Al-Rawi and Fahmy, 2018: 201).…”
Section: Theoretical Framework: Digital Connectivity Migration and Ci...mentioning
confidence: 99%